Local Community Governance in Smart Village Development: A Bibliometric Analysis - Fazira Arni; Sudarmo Sudarmo; Yuliani Sri (E3S Web of Conferences)
To explain about sustainable smart villages, support and cooperation from various parties are needed, both stakeholders, government, and the community. Local communities can be involved in the context of local government in overcoming and identifying various social problems and building cooperation or collaboration through networks with the government to overcome various social problems. This study aims to determine the development of research trends on local community governance in developing smart villages. Research data were taken from the literature available in the Scopus and ScienceDirect databases with a total of 1679 documents and analyzed using bibliometric methods to examine local community governance in publications on smart village development. The results of the study show that research on local community governance in developing smart villages has increased since it was first published in 2000 to 2024. This topic is interesting because it is related to environmental science, and local communities play an important role in smart village development efforts.